10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
There is limited epidemiologic data on varicella zoster virus (VZV) infections from low- and middle-income countries including Kenya. We aimed to describe the seroepidemiology of VZV in Kilifi, Kenya, where varicella vaccine is not included in the national infant immunization program, in order to generate evidence to inform vaccine policy. We conducted a retrospective serosurvey utilizing archived plasma and serum samples from cross-sectional population-based serosurveys conducted within the Kilifi Health and Demographic Surveillance System between 2009 and 2021. We assayed immunoglobulin G (IgG) for VZV using a validated Luminex multiplex immunoassay and applied a seropositivity cutoff of ≥0.26 International Units per millilitre (IU/mL), as determined by the assay developer. We calculated Bayesian-adjusted age-specific seroprevalence and tested differences in seroprevalence between groups using Chi square. We used a multivariable logistic regression model to estimate associations with VZV IgG antibody seropositivity. We fitted an age-dependent catalytic model to estimate the force of infection (FOI) in children aged 0.5-4, 5-9 and 10-14 years. A total of 2639 samples from children aged <15 years and 546 samples from persons aged ≥15 years were tested. The overall population-weighted seroprevalence of VZV IgG antibodies among children aged 0-14 years was 38.4% (95% CI 27.5-49.5). Age-specific seroprevalence rose from 13.3% (95% CI 5.8-21.6) in children aged 0-4 years to 60.9% (95% CI 45.0-76.2) in those aged 10-14 years. Survey year and age were associated with VZV IgG antibody seropositivity. Children aged 5-9 years had the highest FOI (0.098; 95% CI 0.077-0.120) per susceptible year while mean age of infection was 24.3 years (95% CrI 17.6-30.1). Approximately 40% of individuals entering adulthood in Kenya remain susceptible to VZV infection, suggesting a substantial and underappreciated risk of severe VZV disease in older population including pregnant women. An infant varicella immunization program might avert disease across both paediatric and adult populations.